Repurposing of potent drug candidates for multiparasite targeting - Jain, V; Sharma, A (Cell Press, 2017)
Parasite-directed drug discovery efforts require sustained and substantial scientific resources. Many eukaryotic parasites share similarities in metabolic pathways and housekeeping genes, as evident from their underlying protein sequences. Their subsequent structural congruence within enzyme active sites can thus be leveraged for multiparasite targeting using similar or identical drug probes. This bodes well for delivering new anti-infectives.